Prevention of sudden cardiac death in young athletes: Controversies and conundrums - Rowland, T. (The Elite young athlete, 2011)
Strategies for preventing sudden cardiac death in young athletes are predicated on the assumption that: (1) these events reflect pre-existing, clinically silent heart disease, and (2) means for detecting these abnormalities on the pre-participation evaluation are both feasible and accurate. Recent controversy has surrounded both of these presumptions. Some evidence suggests that the myocardial hypertrophy accompanying sports training itself might serve as a substrate for fatal arrhythmias. As well, vigorous debate has arisen over the optimal content of the pre-participation evaluation, particularly regarding the inclusion of routine screening electrocardiograms. As the rarity of these fatal events does not lend itself to an experimental approach, such disagreements are not easily resolved. Consequently, it is expected that decisions regarding approaches to prevention of sudden death in athletes will be dictated largely by region-specific financial, political, and cultural factors. This chapter examines the aetiologies of sudden cardiac death in young athletes as well as the controversies surrounding the prevention of these tragedies.